Effects of Circular RNA of Chicken Growth Hormone Receptor Gene on Cell Proliferation - Xu, Haidong; Leng, Qiying; Zheng, Jiahui; Adu-Asiamah, Patricia; Lin, Shudai; Li, Ting; Wang, Zhang; An, Lilong; Zhao, Zhuihui; Zhang, Li (Frontiers in Genetics, 2021)
Animal growth and development are regulated by neural and endocrine growth axes, in which cell proliferation plays key roles. Recently, many research showed that circular RNAs were involved in hepatocytes and myoblast proliferation. Previously, we identified a circular RNA derived from the chicken GHR gene, named circGHR. However, the function of circGHR is unclear. The objective of this study was to investigate circGHR expression pattern and its roles in cell proliferation. Results indicated that circGHR was a closed-loop structure molecule, and it was richer in the nucleus of hepatocytes and myoblast. Real-time PCR showed that circGHR was increased from E13 to the 7th week in the liver while decreased in the thigh and breast muscle. CCK-8 assay displayed circGHR promoted cell proliferation. Simultaneously, biomarker gene PCNA, CCND1, CDK2, and the linear transcripts GHR and GHBP were upregulated when circGHR overexpressed. Altogether, these data exhibited that circGHR could promote cell proliferation possibly by regulating GHR mRNA and GHBP expression.